Etika Bisnis, Orientasi Manajemen Stakeholders, Pengambilan Keputusan Manajer dan Budaya Perusahaan Kaitannya dengan Peningkatan Tanggung Jawab Sosial Perusahaan dan Kinerja Perusahaan - Sedyastuti, Kristina (Universitas Brawijaya, Indonesia, 2008)
Corporate social responsibility will be an important to give sustainable contribution and beneficial impact upon productivity of corporate through the stakeholder. In order to increase the role of corporate so it is need to develop some factor supports that will be basically push personal decision maker who involving to make decision of corporate social responsibility. There are some facior supports such as business ethic that giving guidance attitude to the corporate decision maker to do its responsibility and giving mutual as well beneficial impact upon the society (Deontological ethic and Utilitarianism). That is also in order to customizing of the corporate culture done responsible by stakeholder. This goal orientation is done in order to support the productivity of the corporate so that corporale making good beneficial impact and profit. It would increase corporate cost in the short time but in the long term it can take very good beneficial impact because through doing corporate social responsibility can also give the value added to the internal corporate such as consumers, user, employers, suppliers, stockholders and owners. To the external corporate such as local government and close society where living around the corporate operation located who would get the social beneficial impact. In real estate especially to those corporate that doing business on the housing project is very good research object because housing development need very wide financial capital, heavy work and involving many employers and giving great impact upon the environment. That is why the member of REI (the Indonesian Real Estate Member) in local east Java as research object because they have been registered as the member therefore they have to follow the ethical conduct of the organization.